THE MAPPING OF MEDIATING NEGATIVE WASHBACK OF THE NATIONAL EXAMINATION - Maya Puspitasari; Muhammad Arifin Pelawi (Eltin Journal : Journal of English Language Teaching in Indonesia, 2023)
The washback study is sorely necessary in the situation of the National Examination system, which selects candidates for the next level of education, due to its gatekeeping role in influencing test-takers' academic futures and supposedly life courses and in allocating power and instituting social order. This qualitative study explores the impact of the Indonesian national examination and how the washback interlinks students, teachers, and parents. The research aims to uncover (1) the objective of the national examination, (2) the washback impact of this high-stake test on students, teachers, and parents, (3) how teachers and parents perceived to be under pressure from the national examination while affecting the students as test-takers. This case study examined the three actors as stakeholders at play through the lens of the parents, teachers, and students as test-taker by conducting semi-structured interviews with teachers and parents and also focus group discussion with students. We probe their Indonesian National Examination experiences based on their beliefs and practices as individuals or professionals. The findings indicated that the objectives of the national examination for the participants were for determining not only the students’ future but also teachers and schools. It then led the participants to have high level of anxiety in facing the national examination. Their practices of teaching, learning and parents were heavily influenced by the national examination.